Contextos para argumentar: uma abordagem para iniciacao a prova no EM utilizando P.A - Eduardo, Antonio Carlos (2007)
This research invests in the conception of learning environments aimed to contribute to the creation of a culture of argumentation, proving and proof in mathematics classrooms. It developed within the context of the project AProvaME as part of the exploration of how to initiate students into aspects of the proving process in relation to the topic of Arithmetic Progressions. In designing this learning environment, we sought contributions from the studies of Bordenave from the areas of the Communication Science and in the field of Mathematics Education, from research relatied to argumentation and in particular the work of Bolite Frant and Castro and of Maher. These contributions enabled the elaboration of an interactive environment for the mediation of mathematical ideas. One of the roles of mediation within the study focuses, in the light of Communication, on the action of the teacher during the negotiation of the mathematics presented in the classroom. Aspects related to socialisation, interaction and mediation were inspired by the constructionist proposal of Papert and other constructionist thinkers. On the basis of these studies, an approach was adopted to the use of technology involving the conception of visual objects embedded within activities aiming to support the development of certain habits of mathematical thinking delineated by Goldenberg. This qualitative study made use of didactic resources such as as the dynamic of games and the use of the computer to promote interaction and the emergence of scenarios for medication. The instruments used in the collection of data Blogs and video recordings valorised the interpretation of the dialogs which occurred within these scenarios. The use of Blogs, still not well documented in research in Mathematics Education, served to show the evolution of mathematical fluency in the arguments produced by the students and also acted as a parameter on the practice of the educator. Editing of the videos collected, permitted the formatting of fragments of registers from the dialogs in the form of cartoon strips, which came to represent a product with a wide range of possible uses both in the interpretation of dialogs and in reflections about the role of the teacher. The results obtained in this study led to recommendations for the creation of new contexts for argumentation